Design and identity: "Absolutely Cusco": A graphic discourse on the power of the local - Radulescu, Mihaela (2006)
Visual communication has taken the city by storm: it informs and seeks to persuade; but, above all, it forms the community. It forms his memory, his imagination, his tastes and his reactions. In public and private spaces, visual -and audiovisual- messages exert a latent power over individuals, which has consequences in the short, medium and long term.